Melatonin involves hydrogen sulfide in the regulation of H+-ATPase activity, nitrogen metabolism, and ascorbate-glutathione system under chromium toxicity. (15th April 2023) - Khan, M. Nasir; Siddiqui, Manzer H.; Mukherjee, Soumya; AlSolami, Mazen A.; Alhussaen, Khalaf M.; AlZuaibr, Fahad M.; Siddiqui, Zahid H.; Al-Amri, Abdullah A.; Alsubaie, Qasi D.
Abstract: Contamination of soils with chromium (Cr) jeopardized agriculture production globally. The current study was planned with the aim to better comprehend how melatonin (Mel) and hydrogen sulfide (H2 S) regulate antioxidant defense system, potassium (K) homeostasis, and nitrogen (N) metabolism in tomato seedlings under Cr toxicity. The data reveal that application of 30 μM Mel to the seedlings treated with 25 μM Cr has a positive effect on H2 S metabolism that resulted in a considerable increase in H2 S. Exogenous Mel improved phytochelatins content and H + -ATPase activity with an associated increase in K content as well. Use of tetraethylammonium chloride (K + -channel blocker) and sodium orthovanadate (H + -ATPase inhibitor) showed that Mel maintained K homeostasis through regulating H + -ATPase activity under Cr toxicity. Supplementation of the stressed seedlings with Mel substantially scavenged excess reactive oxygen species (ROS) that maintained ROS homeostasis. Reduced electrolyte leakage and lipid peroxidation were additional signs of Mel's ROS scavenging effects. In addition, Mel also maintained normal functioning of nitrogen (N) metabolism and ascorbate-glutathione (AsA-GSH) system. Improved level of N fulfilled its requirement for various enzymes that have induced resilience during Cr stress. Additionally, the AsA-GSH cycle's proper operation maintained redox equilibrium, which is necessary for the biological system to function normally. Conversely, 1 mM hypotaurine (H2 S scavenger) abolished the Mel-effect and again Cr-induced impairment on the above-mentioned parameters was observed even in presence of Mel. Therefore, based on the observed findings, we concluded that Mel needs endogenous H2 S to alleviate Cr-induced impairments in tomato seedlings.